2021
DOI: 10.1111/ijfs.15402
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of beta‐lactoglobulin/sodium alginate dry films

Abstract: Optimum beta-lactoglobulin/sodium alginate dry films (β-LG/SA(S)) formed from casting solutions containing β-LG 1.25% (w/v) and SA 1% (w/v) showed appropriate characteristics to be easily handled. SEM micrographs showed a less homogeneous microstructure of this films respect to sodium alginate dry films used as control (SA(F)). Tensile strength of 18 MPa and an elongation value of 5% were obtained for β-LG/SA(S). DSC thermograms did not demonstrate changes in thermal properties of SA in presence of β-LG. Studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Besides the occurrence of charge interactions between alginate and β-lactoglobulin, hydrophobic interactions can also be established. Raman spectroscopy analysis revealed that the interactions between WPI and alginate cause conformational changes in WPI; in particular, the ordered structures of α-helixes and β-sheets of WPI were strengthened at pH 4.0 and 5.0 [ 30 , 31 ]. In a further study, the effect of β-lactoglobulin cross-linking using transglutaminase on the binding with alginate was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the occurrence of charge interactions between alginate and β-lactoglobulin, hydrophobic interactions can also be established. Raman spectroscopy analysis revealed that the interactions between WPI and alginate cause conformational changes in WPI; in particular, the ordered structures of α-helixes and β-sheets of WPI were strengthened at pH 4.0 and 5.0 [ 30 , 31 ]. In a further study, the effect of β-lactoglobulin cross-linking using transglutaminase on the binding with alginate was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Whey protein/β-lactoglobuin and alginate mixtures were studied for the production of edible coating and film. Interestingly, the β-lactoglobulin binding properties were maintained in the dry film and after film re-dissolution, which would allow the development of new carriers for food bioactive compounds [ 31 ]. The presence of β-lactoglobulin improved the oxygen barrier properties of the film [ 33 ] but decreased the tensile strength, and hence further studies are required before using these edible films for application in the food industry [ 31 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium alginate (SA) is a natural polysaccharide, consisting of ⊎-D-mannuronic acid (M unit) and ⊍-L-guluronic acid (G unit). 18,19 The Na + in SA can exchange with Ca 2+ , and the G unit can also react with Ca 2+ , resulting in formation of an 'egg-box' network structure. 20 SA-based hydrogels are universally studied to encapsulate bioactive ingredients by the ionic gelation method.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium alginate (SA) is a natural polysaccharide, consisting of β‐ d ‐mannuronic acid (M unit) and α‐ l ‐guluronic acid (G unit) 18,19 . The Na + in SA can exchange with Ca 2+ , and the G unit can also react with Ca 2+ , resulting in formation of an ‘egg‐box’ network structure 20 .…”
Section: Introductionmentioning
confidence: 99%